2020
DOI: 10.1155/2020/8898126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for Thermal Conductivity of Frozen Soil Based on Nonlinear Regression and Support Vector Regression Methods

Abstract: The comprehensive understanding of the variation law of soil thermal conductivity is the prerequisite of design and construction of engineering applications in permafrost regions. Compared with the unfrozen soil, the specimen preparation and experimental procedures of frozen soil thermal conductivity testing are more complex and challengeable. In this work, considering for essentially multiphase and porous structural characteristic information reflection of unfrozen soil thermal conductivity, prediction models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…. SVR was successfully applied in solving engineering problems including hydrocarbon reservoir prediction [62], the thermal conductivity of frozen soil prediction [63], and rock mass parameter [64] prediction. at algorithm is developed from the statistical learning theory, and the input variables were reflected into a high-dimensional space by using the kennel function [65,66].…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%
“…. SVR was successfully applied in solving engineering problems including hydrocarbon reservoir prediction [62], the thermal conductivity of frozen soil prediction [63], and rock mass parameter [64] prediction. at algorithm is developed from the statistical learning theory, and the input variables were reflected into a high-dimensional space by using the kennel function [65,66].…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%
“…Recently, ML algorithms have been applied to estimate the thermal conductivity of soils (Cui et al 2020 ;Zhang et al 2020a ;Zhao et al 2022 ;Li et al 2022b ). Several studies have re vie wed the use of ML algorithms to predict soil thermal conductivity, including Zhao et al ( 2022 ) and Li et al (2022a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Although thermal conductivity of coal powder has been tested by experimental means under atmospheric pressure, there are relatively few studies on the determination of thermal conductivity of underground tar-rich coal seam. Due to the requirement of sophisticated test procedures, experimental measurement of thermal conductivity of underground tar-rich coal seam becomes impractical [6] . Fortunately, prediction models about thermal conductivity of many materials were proposed [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Manoj [8] indicated that support vector machine model has the excellent prediction capability to predict the thermal conductivity of rocks using simple rock parameters. Cui et al [6] demonstrated that the ternary fitting model has a higher thermal conductivity prediction accuracy for 7 types of frozen soils. In fact, thermal conductivity of underground tarrich coal seam is influenced by numerous factors [9][10] .…”
Section: Introductionmentioning
confidence: 99%